The effect of physical characteristics on the price of stocker and feeder cattle - F. Brazle; J. Mintert; Ted C. Schroeder; O. Grunewald (Kansas Agricultural Experiment Station Research Reports, 1988)
A survey of feeder cattle sales was conducted at seven Kansas cattle auctions during 1986 and 1987. A wide variety of physical characteristics was found to influence feeder cattle prices. The price impact resulting from changes in fill and condition varied seasonally. Although calves showing any signs of health problems received severe price discounts, the presence of other undesirable characteristics also resulted in discounts, but to lesser degrees.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen& #x27; s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Stockercattle; Feeder cattle